Factors Affecting Medical Service Quality. - Ali Mohammad Mosadeghrad (Tehran University of Medical Sciences, 2014)
A better understanding of factors influencing quality of medical service can pinpoint better strategies for quality assurance in medical services. This study aimed to identify factors affecting the quality of medical services provided by Iranian physicians.Exploratory in-depth individual interviews were conducted with sixty-four physicians working in various medical institutions in Iran.Individual, organizational and environmental factors enhance or inhibit the quality of medical services. Quality of medical services depends on the personal factors of the physician and patient, and factors pertaining to the healthcare setting and the broader environment.Differences in internal and external factors such as availability of resources, patient cooperation and collaboration among providers affect the quality of medical services and patient outcomes. Supportive leadership, proper planning, education and training and effective management of resources and processes improve the quality of medical services. This article contributes to healthcare theory and practice by developing a conceptual framework for understanding factors that influence medical services quality.